(untitled) (TAJ: Journal of Teachers Association, 2019)
Background: Bangladesh recently became a middle income country and despite of its relatively low skilled birth attendance (26.5%) nevertheless experience a rise in caesarean section (CS) rate. But now the rate of CS increased almost seven fold from 3.5% in 2004 to 23% in 2016. Objective: To find out the cause and incidence of caesarean section among the primigravid mother in Rajshahi medical college hospital performed in between January 2017 to December 2017. Methods: This prospective type of observational study was performed in Rajshahi Medical College Hospital (RMCH) over a period of one year from January 2017 to December 2017. All primigravida who underwent caesarean section in RMCH were included. Result: During the study period there were 11018 deliveries. Overall CS rate was 40.98%. The rate in primi was 30.70% and last year it was 25.58%. Conclusion: The vast majority of CS was not medically indicated. A number of policies and program had been launched to counteract this increasing rate of CS but virtually there was no impact. TAJ 2018; 31(2): 54-58